Construction of Silk Fibroin 3D Microfiber Scaffolds and Their Applications in Anti-Osteoporosis Drug Prediction - Hua Xu; Mengfan Huang; Mengyuan Zhou; Rong Guo; Kunming Qin; Zibo Dong (Molecules)
Silk microfiber scaffolds have garnered increasing interest due to their outstanding properties, with degumming being the process used to extract the sericin from the cocoon. In the present study, an attempt to tune the biodegradation period of silk through degumming with various sodium borohydride (NaBH4) concentrations and degumming times was studied. We considered the process, the number of baths used, and the salt concentration. Herein, we report a novel method of expanding microfibers from two-dimensional (2D) to three-dimensional (3D) using a modified gas-foaming technique. Porous three-dimensional (3D) silk fibroin (SF) scaffolds were fabricated by the SF fibers, which were extracted by the NaBH4 degumming method and NaBH4 gas-foaming approach. This study showed that higher salt concentrations, reaching 1.5% in a double bath, effectively removed sericin from silk fibroin, resulting in clean, smooth 3D scaffolds. These scaffolds were then fabricated using a freeze-drying method. The scaffolds were then submerged in solutions containing semen cuscutae (SC) and their surfaces were coated with various percentages of total flavonoids. The scaffolds had no toxicity to the cells in vitro. This work provides a new route for achieving a TFSC-loaded scaffold; it is proved that the coated silk fibroin fiber scaffold has excellent compatibility. Compared with non-drug-loaded silk scaffolds, drug-loaded silk scaffolds promote cell growth.